INNOVATING LITERARY EDUCATION: A MULTIFACETED APPROACH TO TEACHING FOREIGN LITERATURE IN SCANDINAVIAN COUNTRIES (Comparative Professional Pedagogy, 2024)
In the dynamic field of education, the teaching of foreign literature faces challenges. In Scandinavia, known for high-quality education, innovative methods are crucial for instilling a deep appreciation for global literary works. This article explores diverse approaches to enhance engagement, cultural understanding and critical thinking among students. Leveraging audio-visual resources, including videos and interactive presentations, creates a vibrant learning environment in Scandinavian classrooms. This fosters a deeper connection between students and foreign literature, resonating with the tech-savvy younger generation. In embracing the digital age, teachers use online platforms and tools like discussion forums and virtual book clubs to encourage interactive engagement. These digital tools enhance critical thinking and analytical skills by exploring diverse perspectives. Immersive VR literature tours allow students to virtually step into the settings of foreign literary works, providing a unique and memorable learning experience. This stimulates creativity and deepens understanding of cultural and historical contexts. Recognizing language diversity, utilizing high-quality translations broadens access to foreign literature. This inclusive approach allows students to appreciate literary expression across linguistic boundaries. Guiding students in creating digital storytelling projects using podcasts, videos, and blogs enhances creativity and communication skills. This hands-on approach prepares students for the modern digital world. Infusing play into literary education through quizzes and interactive simulations makes the study of foreign literature enjoyable and engaging. In conclusion, innovative methods in Scandinavian countries aim to cultivate globally aware individuals. These multifaceted approaches not only enhance the study of foreign literature but also foster critical thinking, cultural understanding, and a lifelong love for literature. By integrating multimedia, embracing digital tools, and promoting interactive learning, teachers in Scandinavia ensure their students embark on a literary journey that transcends borders, enriching their intellectual and cultural horizons in an evolving educational landscape.
Keywords: innovation; literary education; teaching foreign literature; Scandinavian countries; Ukraine